2022
DOI: 10.1021/acsomega.2c01395
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Agroclimatic Variables on Proteogenomics in Sugar Cane (Saccharum spp.) Plant Productivity

Abstract: Sugar cane ( Saccharum spp. hybrids) is a major crop for sugar and renewable bioenergy worldwide, grown in arid and semiarid regions. China, the world’s fourth-largest sugar producer after Brazil, India, and the European Union, all share ∼80% of the global production, and the remaining ∼20% of sugar comes from sugar beets, mostly grown in the temperate regions of the Northern Hemisphere, also used as a raw material in production of bioethanol for renewable energy. In view of carboxylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 131 publications
1
9
0
Order By: Relevance
“…Internodes 11 and 12 of all selected transgenic lines yielded maximum SRPin comparison to lower SRP happened in juvenile internodes. Similar reports indicated that better SRP can be obtained in internode number 10 as appeared in current studies 45 . Another interesting feature was also analyzed and experienced in all nine lines exhibiting TH > 700 mM.…”
Section: Discussionsupporting
confidence: 90%
“…Internodes 11 and 12 of all selected transgenic lines yielded maximum SRPin comparison to lower SRP happened in juvenile internodes. Similar reports indicated that better SRP can be obtained in internode number 10 as appeared in current studies 45 . Another interesting feature was also analyzed and experienced in all nine lines exhibiting TH > 700 mM.…”
Section: Discussionsupporting
confidence: 90%
“…The study found that the changes in gs of sugarcane seedlings after smut infection were insignificant. It is considered that there are two main reasons for the decline of Pn; stomatal and non-stomatal factors are mainly affected by the regulation mechanism [ 2 , 5 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sugarcane is an important bioenergy crop grown worldwide. Its sugar production accounts for 80% of global sugar production and 92% of China’s total sugar production [ 1 , 2 ]. Disease is one of the main factors causing the loss of sugarcane yield and sugar content [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In European countries, beet sugar produces up to 80% of the total collection in the world [6]. China, the world's fourth-largest sugar producer after Brazil, India, and the European Union, 20% of sugar comes from sugar beets [7]. Sugar beet requires an abundance of sun, warmth and moderate humidity, therefore, in the Russian Federation, the cultivation of this crop is concentrated in the southern regions.…”
Section: Introductionmentioning
confidence: 99%
“…Sugar beet requires an abundance of sun, warmth and moderate humidity, therefore, in the Russian Federation, the cultivation of this crop is concentrated in the southern regions. On the lands of the Krasnodar region, the Volga and Chernozem regions, 51% of the total sugar beet is grown [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%